2020
DOI: 10.3389/fpsyt.2020.00474
|View full text |Cite
|
Sign up to set email alerts
|

The Senses of Agency and Ownership in Patients With Borderline Personality Disorder

Abstract: Patients with borderline personality disorder (BPD) not only experience a strong instability in their affect and interpersonal relations but also disturbances in their self-experience, including dissociation and body-alienation symptoms. It is not yet understood whether an altered sense of ownership (SoO) or sense of agency (SoA) may contribute to these disturbances. One recent hypothesis is that patients with BPD have a reduced sense of self and are therefore more likely to misattribute external objects or ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 53 publications
(106 reference statements)
2
15
0
1
Order By: Relevance
“…Regarding our correlation analysis, we found a weak positive correlation (r = 0.318) between SoO and SoA across conditions. This finding is in line with previous studies (Kalckert and Ehrsson, 2012;Braun et al, 2014;Möller et al, 2020;Spychala et al, 2020) and suggests that both subjective measures do not assess completely distinct, but rather overlapping aspects of selfexperience, or that SoO and SoA promote each other (Braun et al, 2018).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Regarding our correlation analysis, we found a weak positive correlation (r = 0.318) between SoO and SoA across conditions. This finding is in line with previous studies (Kalckert and Ehrsson, 2012;Braun et al, 2014;Möller et al, 2020;Spychala et al, 2020) and suggests that both subjective measures do not assess completely distinct, but rather overlapping aspects of selfexperience, or that SoO and SoA promote each other (Braun et al, 2018).…”
Section: Discussionsupporting
confidence: 91%
“…This spatial constraint falls in line with several other identified top-down constraints that a perceptual object has to fulfil to become embodiable and identified as "mine" (Braun et al, 2018). A RHI is typically not inducible, for example, if the artificial hand is placed in an anatomically-implausible position (Ehrsson et al, 2005a;Kalckert and Ehrsson, 2012;Braun et al, 2014;Möller et al, 2020), or if a non-hand object is used instead of an artificial hand (Haans et al, 2008;Tsakiris et al, 2010). Following Tsakiris (2010) classification, according to which most SoO theories can be situated in a continuum ranging from bottom-up to top-down accounts, the present results rather support top-down theories of SoO.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Two recent experiments in BPD show contrasting results: an experiment using the Sensory Attenuation paradigm suggest that this implicit measure of SoA is abnormally decreased in a subgroup of BPD patients without non-suicidal self-injury ( 96 ). Another experiment using an intentional binding paradigm incorporated into a modified RHI paradigm provided evidence for higher self-reported SoA, but no conclusive evidence of an impaired implicit measure of SoA ( 45 ). However, these preliminary results should be interpreted with caution given their methodological limitations and lack of statistical power.…”
Section: The Acting Self: Why Agency Is Importantmentioning
confidence: 96%
“…Two studies report an increased illusory limb ownership in adult women with BPD compared to healthy controls ( 43 , 44 ). A third study using a modified version of the RHI did not replicate this finding ( 45 ). Interestingly, one of these studies showed that this increased illusion occurred not only in the synchronous condition, but also in the asynchronous condition ( 44 ).…”
Section: Introductionmentioning
confidence: 98%